From rhetoric to reality: How ideology, history and geography shape populism's economic footprint - Piergiuseppe Fortunato; Tanmay Singh; Marco Pecoraro (University of Neuchâtel, Institute of Economic Research (IRENE), 2024)
We examine the policy changes enacted by populist leaders after coming into power in different historical and geographical contexts. We employ the dataset developed by Funke et al. (2023), based on Cas Mudde's minimalist definition of populism, and expand it to several additional policy dimensions. We find that populist governance is rather heterogeneous both in terms of policy instruments and outcomes, and that it varies depending on historical context, geography, and ideology. We conclude that we should contemplate a more nuanced definition of populism for a better understanding of the phenomenon.
Keywords: D60; E60; N10; P16; 330; Populism; Public expenditure; Corruption